Taxonomic reassessment and redescription of Scolopendra arthrorhabdoides Ribaut, 1913, with a discussion on its related species (Scolopendromorpha, Scolopendridae) - Chagas-Jr, Amazonas; Jiménez, Sebastián Galvis (Zootaxa, 2018)
Scolopendra arthrorhabdoides Ribaut, 1913 is redescribed based on fresh material. Its taxonomic status is evaluated and compared with Scolopendra armata Kraepelin, 1903 and Scolopendra alternans Leach, 1816. The geographical distribution of S. arthrorhabdoides is also revised. Scolopendra armata is reported from Colombia for the first time.